2022
DOI: 10.1002/pc.26872
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal and microstructural studies of acrylonitrile butadiene styrene reinforced with rattan (Calamus beccarii) fiber composites

Abstract: In this research work, fibers from rattan plant stem (RA) were selected as reinforcing material with widely used thermoplastic polymer acrylonitrile butadiene styrene (ABS). The extracted fibers were chemically modified with NaOH followed by benzoylation and bleaching. Then they were used as reinforcement in ABS polymer matrix by different weight percentages (0, 10, 20, 30, and 40 wt%) for fabrication of composites. It was observed that chemical treatment changes the surface texture of the fibers enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The characterization of the product from the perspective of thermal analysis is essential for estimating stability in terms of changes in temperature and kinetic parameters when referring to thermogravimetric analysis (TGA) [ 23 ]. In several studies, this has been implemented as the main requirement for identifying the thermal stability of materials and determining the degradation peaks (the temperature at which degradation is maximal) [ 24 , 25 , 26 , 27 ], and used as a useful tool for estimating drying temperatures [ 26 ]. Another thermal analysis technique is differential scanning calorimetry (DSC), a method in which the difference in heat flux rate between the reference material and the product being evaluated is estimated as a temperature element, while the substance and the reference are subjected to a manageable temperature program ranging from subzero to high temperatures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the product from the perspective of thermal analysis is essential for estimating stability in terms of changes in temperature and kinetic parameters when referring to thermogravimetric analysis (TGA) [ 23 ]. In several studies, this has been implemented as the main requirement for identifying the thermal stability of materials and determining the degradation peaks (the temperature at which degradation is maximal) [ 24 , 25 , 26 , 27 ], and used as a useful tool for estimating drying temperatures [ 26 ]. Another thermal analysis technique is differential scanning calorimetry (DSC), a method in which the difference in heat flux rate between the reference material and the product being evaluated is estimated as a temperature element, while the substance and the reference are subjected to a manageable temperature program ranging from subzero to high temperatures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highest tensile strength of 74.98 MPa, 4.80 GPa of young's modulus, 10 MPa of flexural strength and 31.42 kJ/m 2 of impact strength were obtained at optimum fiber loading (24 wt%). [19] Nayak studied the physical, mechanical, and thermal properties of Pennisetum orientale grass fiber filled vinyl ester composites. [20] They found that 25 wt% of fiber content reveals highest mechanical as well as better thermal properties.…”
Section: Introductionmentioning
confidence: 99%